2005
DOI: 10.1002/hyp.6004
|View full text |Cite
|
Sign up to set email alerts
|

Are headwaters just the sum of hillslopes?

Abstract: Until recently, there have been few attempts to link hillslope, headwater and meso-scale hydrology. However, the paper by Shaman et al. (2004, Hydrological Processes 18: 3195-3206) has proposed concepts that link headwater and meso-scale basins. Although their paper provides an excellent example of how we should make connections between small-and large-scale hydrology, the analysis still lacked sufficient consideration of the spatial variability of hydrological behaviour at the hillslope/headwater scale. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 33 publications
4
95
0
Order By: Relevance
“…Our findings confirmed the statement of Keller et al (1989) who postulated that baseflow originates from deep percolating water from springs based on sampling at the catchment outlet. Uchida et al (2005) made similar observations in steep, homogeneous and forested headwaters in Japan. Inamdar et al (2013) found from changes in hydrochemistry that during seasonal drying over the summer (in dry conditions), portions of the drainage network were disconnected and did not contribute to streamflow.…”
Section: Wider Implications On Pre-alpine Baseflowsupporting
confidence: 61%
“…Our findings confirmed the statement of Keller et al (1989) who postulated that baseflow originates from deep percolating water from springs based on sampling at the catchment outlet. Uchida et al (2005) made similar observations in steep, homogeneous and forested headwaters in Japan. Inamdar et al (2013) found from changes in hydrochemistry that during seasonal drying over the summer (in dry conditions), portions of the drainage network were disconnected and did not contribute to streamflow.…”
Section: Wider Implications On Pre-alpine Baseflowsupporting
confidence: 61%
“…Several studies have documented structured trends in stream chemistry that become apparent as basin scale increases [Wolock et al, 1997;Shaman et al, 2004;Temnerud and Bishop, 2005;Uchida et al, 2005]. Since this behavior seems to be a common occurrence, streamflow chemistry may be particularly useful in linking process understanding across multiple scales.…”
Section: Introductionmentioning
confidence: 99%
“…Much experimental work on understanding hydrological processes has been done in temperate, humid climates using either single or multi-method approaches (e.g. Uchida et al, 2005;Blume et al, 2008;Uhlenbrook et al, 2002Uhlenbrook et al, , 2008. However, experimental hydrology and processrelevant studies in the predominantly data scarce semi-arid regions of SSA or Central Asia are, due to mostly logistical and financial constraints, less widespread (e.g.…”
Section: Introductionmentioning
confidence: 99%